Polyunsaturated fatty acid metabolism in the retinal pigment epithelium and its association with outer retinal disease - Naga Pradeep Rayana; Navdeep Gogna; Mark P. Krebs; Gayle B. Collin; Jürgen K. Naggert; Patsy M. Nishina (Mammalian Genome, 2026)
Polyunsaturated fatty acids (PUFAs) are essential for photoreceptor (PR) development, structure and function, and their availability in the outer retina is predominantly mediated by the retinal pigment epithelium (RPE), a cellular monolayer juxtaposed to the PR outer segments. Because PRs lack enzymatic machinery to generate critical PUFA intermediates from dietary precursors, they rely on the RPE to coordinate multiple steps of PUFA uptake, metabolism and export. Consequently, disruption in any of these steps perturbs PR homeostasis and compromises overall retinal health. In this review, we summarize current evidence about the genes, proteins, molecular pathways, and pathological alterations that govern the regulation of PUFA metabolism in the RPE. Data from human genetic disorders, mouse models and in vitro studies is discussed to illustrate how disruption of PUFA pathways in the RPE leads to lipid imbalance and retinal degeneration, and to highlight how these findings illuminate molecular mechanisms underlying PUFA biology. We also identify critical gaps in knowledge and unresolved questions surrounding RPE-PR PUFA metabolism and propose that addressing these gaps will be essential for advancing therapeutic strategies for retinal disease.

A novel ENU-induced mutation, peewee, causes dwarfism in the mouse - Bokryeon Lee; Kiyoshi Kano; Jay Young; Simon WM. John; Patsy M. Nishina; Jurgen K. Naggert; Kunihiko Naito (Mammalian Genome, 2009)

A novel ENU-induced mutation, peewee, causes dwarfism in the mouse - Lee Bokryeon; Kiyoshi Kano; Jay Young; Simon W. M. John; Patsy M. Nishina; Jurgen K. Naggert; Kunihiko Naito (Mammalian Genome, 2009)

Mapping of genetic modifiers of Nr2e3 rd7/rd7 that suppress retinal degeneration and restore blue cone cells to normal quantity - Neena B. Haider; Weidong Zhang; Ron Hurd; Akihiro Ikeda; Arne M. Nystuen; Jürgen K. Naggert; Patsy M. Nishina (Mammalian Genome, 2008)